The Explicit Expression of the Drazin Inverse and Its Application - Xiaoji Liu; Shaowu Huang; Liang Xu; Yaoming Yu (Journal of Applied Mathematics)
We give explicit expressions of (P±Q)d of two matrices P and Q, in terms of P, Q, Pd, and Qd, (P±I)d, under the condition that PQ=P, and apply the result to finding an explicit representation for the Drazin inverse of some 2×2 block matrix.